2021
DOI: 10.3390/genealogy5020056
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m Not Swedish Swedish’: Self-Appraised National and Ethnic Identification among Migrant-Descendants in Sweden

Abstract: As a country of high migration, Sweden presents an interesting case for the study of belongingness. For the children of migrants, ethnic and national identification, as well as ascriptive identity, can pose challenges to feelings of belongingness, which is an essential element for positive mental health. In this article, survey data were collected from 626 Swedes whose parents were born in the following countries: Somalia, Poland, Vietnam, and Turkey. The results show that Poles significantly felt they receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…By acknowledging mentees’ strengths, the EMPOWER program enabled mentees to confirm their inner identity and, at the same time, promoted a sense of place in Australia. This aligns with Adolfsson (2021), who studied migrants’ sense of belonging in Sweden and found that ‘multiple memberships between groups need not be contradictory but rather an expression of different spheres of inhabitance’ [ 45 ]. A sense of belonging is a key component of mental health [ 45 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…By acknowledging mentees’ strengths, the EMPOWER program enabled mentees to confirm their inner identity and, at the same time, promoted a sense of place in Australia. This aligns with Adolfsson (2021), who studied migrants’ sense of belonging in Sweden and found that ‘multiple memberships between groups need not be contradictory but rather an expression of different spheres of inhabitance’ [ 45 ]. A sense of belonging is a key component of mental health [ 45 ].…”
Section: Discussionsupporting
confidence: 79%
“…This aligns with Adolfsson (2021), who studied migrants’ sense of belonging in Sweden and found that ‘multiple memberships between groups need not be contradictory but rather an expression of different spheres of inhabitance’ [ 45 ]. A sense of belonging is a key component of mental health [ 45 ].…”
Section: Discussionsupporting
confidence: 79%